Journals of the first, second and third voyages for the discovery of a North-west Passage from the Atlantic to the Pacific, in 1819-20-21-22-23-24-25, in His Majesty's ships Hecla, Griper and Fury, under the orders of Capt. W.E. Parry, R.N. F.R.S. and commander of the expedition [electronic resource]. - Parry, William Edward, Sir, 1790-1855. (London : J. Murray, 1828)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 40394-40399. "Five volumes. Vol. I." Electronic reproduction. Mode of access: Internet. 44